2022
DOI: 10.1111/padr.12467
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Education on Child Mortality in Bangladesh

Abstract: This paper examines the effect of maternal education on child mortality in Bangladesh by exploiting quasi‐experimental variations in the duration of exposure to a school stipend project for identification. Results from the instrumental variable estimation indicate that an additional year of maternal schooling reduces both under‐five and infant mortality by about 20 percent. The findings are statistically significant and robust to a number of model specifications, including survival models controlling for right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The downward trend of vitamin A supplementation (73% in 1999–38% in 2004) among children aged 9–11 months indicated the deficiency of vitamin A in their early stage of life, might be a reason for increased ARI prevalence during 1996–2004 23 . In Bangladesh, the child mortality rate was much higher at the decade of independence in 1971 24 . The cause behind this was various infectious diseases 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The downward trend of vitamin A supplementation (73% in 1999–38% in 2004) among children aged 9–11 months indicated the deficiency of vitamin A in their early stage of life, might be a reason for increased ARI prevalence during 1996–2004 23 . In Bangladesh, the child mortality rate was much higher at the decade of independence in 1971 24 . The cause behind this was various infectious diseases 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…23 In Bangladesh, the child mortality rate was much higher at the decade of independence in 1971. 24 The cause behind this was various infectious diseases. 25,26 Since then, Bangladesh government had been started an extensive immunisation programme (EPI) across the country in order to protect the child from these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between education, including female education, and population health outcomes has also been investigated, and the results indicated that female education has a beneficial influence on the health of the population, as measured by maternal health, neonatal mortality, under-five, and infant mortality [ 5 , 45 , 94 , 103 ]. However, to the best of our knowledge, the current study is the first conducted in SSA to examine the transmission mechanisms of PHS by using growth factor variables and LGCMM.…”
Section: Discussionmentioning
confidence: 99%
“…The covariates used for this study are residence, nature of the child, sex of the child, mother follow-up, place of antenatal care, place of child delivery, breastfeeding from the breast only, a child infected with malaria, the child suffered from malnutrition, the child suffered from septicemia, a child suffered from cough and child suffered from pneumonia. The variables classi cations used in the current study were suggested by many previous studies [15,16,17,18,19,20,21,22,23,24]…”
Section: Independent Variablesmentioning
confidence: 99%